The Role of “Problematic” and “Improved” Indicators of Risky Lifestyles in the Self-Control/Lifestyle Framework of Victimization Among Filipino Adolescents - Barrera, Dan Jerome (Asian journal of criminology, 2018)
Pratt and Turanovic (European Journal of Criminology, 13(1):129-146, 2016) argue that previous studies operationalizing risky lifestyles as mere “going out” (problematic indicators of risky lifestyles) were misspecified and that “improved” indicators of risky lifestyle (risky behaviors) would perform better than “problematic” indicators in models that explain victimization. This study examines these propositions by testing the self-control/lifestyle framework of victimization using the data from a random sample of Filipino high school students at a state university in Dumaguete City, Philippines. Results show strong support to Pratt and Turanovic’s claims. Self-control has stronger effects on improved indicators than on problematic ones. And, improved indicators have stronger effects than problematic indicators on property, violent, peer/sibling and sexual victimization. Moreover, the findings provide partial support for the self-control/lifestyle framework of victimization.